Pengembangan Buku Saku Biologi SMA Materi Sistem Ekskresi Manusia Kelas XI (Uji Coba di SMAN 2 Lembang Jaya) - Yulinda Fitriani; Afrahamiryano Afrahamiryano; Asmawati Kamal (Eduscience Development Journal, 2019)
This research is based on the background because the books in the school have not facilitated the students in learning. The purpose of this research is to produce a valid and practical pocket book. This type of research is research development (Research and Development), by using development model of ADDIE (Analysis, Design, Development, Implementation, and Evaluation). The instrument used is a questionnaire of material experts, linguists, teacher responses, and student responses. The subjects of the experiment were 22 students of class XI SMA Negeri 2 Lembang Jaya. Pocket book media development through five stages. The first stage of analysis is: curriculum analysis on the subject matter of the Human Excretion System, a handbook that has not yet facilitated the students. Second stage: preparation of media framework, systematic presentation of media, and instrument planning. The third stage of product making based on stayboard, revising the product based on input from validation experts. The fourth phase of product trial. The fifth stage of evaluation of the test results. Based on the data analysis, validation questionnaire of material and language experts reached 81% and 88.50%. Praktikalitas by students who reach 82% and teachers 89.63%. Based on these stages, then the media produced pocket book Biology on the material of Human Excretion System is valid and practical.